CRITICAL STUDY ON LEGAL THINKING OF MUHAMMAD SHAHRUR - Havis Aravik; Choiriyah Choiriyah; Saprida Saprida (AHKAM : Jurnal Ilmu Syariah, 2018)
Syahrur is a controversial thinker from Syria who offers a new epistemological base on the Theory of the Boundary (Nadzariyah Al-Hudud), in response to the stagnation of the study of Islamic legal thought, as well as a critique of the literal and rational groups that always dwell on the revelation and reason to provide modernity to its people. The thought of the Syharur reaped much criticism and blasphemy even in some of the country's books forbidden to read and circulate. But Western academics give full appreciation because Syahrur managed to continue the work that has not been done Fazlur Rahman with his double movement.In Boundary Theory (Nadzariyah Al-Hudud), Shahrur distinguishes between the prevailing limits of worship and the limits applicable in the al-hudud theme. For Shahrur, worship in the sense of the relationship between human and God that is tawqifiyah, consists of four categories only, namely prayer, zakat, fasting Ramadan, and hajj for the capable. Such forms have been finalized after being perfected by Islam and inviolable. While there are several possible forms for the development of law, Syahrur divides it into 6 theoretical models of maximum and minimum limits.  Keywords; Syria, dialectics, Nadzariyah Al-Hudud, Pluralism, Polygamy